267 TIME DEPENDENCE OF HEPATIC STELLATE CELL CONTRACTILE FORCE GENERATION. (1st January 2006) - Datta, A.; Martinez, L.; Melton, A. C.; Yee, H. F.
Abstract : The contractile force generated by hepatic stellate cells (HSCs) contributes to the liver's injury response. It has been postulated that HSC contractility increases with time of injury. Our aim was to test this hypothesis by directly quantitating contractile force generation by HSCs in primary culture, a well-characterized liver injury model. Method: HSCs were grown in primary culture for 1, 4, 8, and 12 days prior to experimentation to simulate the injury response. One million HSCs were placed within a 3-dimensional collagen gel for 3 days, attached to a force transducer, and mounted in an organ bath containing serum-free media for 1 hour. Gels containing HSCs were stimulated with 2 nM endothelin 1 (ET). Force development was recorded digitally. Select gels were then fixed, and microscopic cross-sections were cut and stained with toluidine blue. Micrographs were taken and the number of cells within each cross-section was determined. Results: 2 nM ET-stimulated HSC contractile force development in a dose-dependent manner (Table). The number of HSCs in each cross-section was time dependent (Table). Conclusion: We have for the first time directly measured the force generated by HSCs after a range of days in culture. Both the force of contraction and the number of cells within a cross-section of a gel increased with the number of days in culture. This suggests that the time-dependent increase in force generation may be due to an increase in HSC number rather than an increase in force generated by each cell.